The Effect of Globalization on Islamic Laws in Malaysia: (Kesan Globalisasi terhadap Guna Pakai Undang-undang Islam di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2017)
The process of globalization has increased the pressure to apply international legal provisions onto municipal laws. This hegemonzation process emphasizes universal features which are being opposed and thus not accepted by all. Western colonization and the transfer of legal systems related to globalization marginalize indigenous norms including Islamic laws. Among the main questions being raised is the status of Islamic laws which are viewed as being contrary to the provisions of international treaties. This article uses doctrinal analysis and textual analysis including those involving legislation and cases in the process of search and argument over related legal principles. Among the findings in this article is that the dualism principle which is applicable in Malaysia in respect of the application of international laws requires the transformation of international treaties to municipal law. In other words, treaties are not directly applicable to municipal law.Keywords: globalization, Islamic laws, challenges, hemegonization